The concept of tolerance in the minds of the youth of Uzbekistan the uniqueness of its formation. - Mamirov Azizjon Niyazmukhamedovich (Zien Journals, 2022)
This article highlights the need to preserve national identity in Uzbekistan in the modern era of globalization and their positive and negative consequences in the life of society. The essence of the policy pursued in our republic is shown to broad propaganda on the formation of a tolerant worldview in the minds of our people, the principles of equality and tolerance in Uzbekistan.
Keywords: Tolerance, globalization, mass culture, youth, globalization, spirituality, idea, nationalism, information, technology, equality